Childhood Trauma, Personality, and Substance Use Disorder: The Development of a Neuropsychoanalytic Addiction Model - Fuchshuber, Jürgen; Unterrainer, Human Friedrich (Frontiers in Psychiatry, 2020)
Background: While traditional psychoanalysis has been criticized as insufficient for the treatment of substance use disorder (SUD), recent progress in the field of neuropsychoanalysis has generated new and promising hypotheses regarding its etiology. However, empirical research applying this framework has been sparse. Aim and Scope: The present overview aims at developing and empirically validating a neuroscientifically informed psychodynamic framework regarding the etiology of SUD. For this purpose, this review provides a concise overview of the most relevant historical and contemporary psychoanalytic theories on SUD etiology. Furthermore, the original research summarized in this paper consists of three studies investigating connections between childhood trauma, primary emotions, personality structure and attachment, as well as their relation to SUD development and treatment. Conclusions: The results highlight the empirical validity of the neuropsychoanalytic approach towards SUD etiology. In particular, the findings underscore the conceptualization of SUD as a disorder related to dysfunctional attachment and affect regulation abilities especially linked to increased SADNESS and ANGER dispositions, which mediated the relationship between SUD and traumatic childhood relationships. Based on these findings, a refined model of SUD etiology is proposed, which should be tested in future studies.